Multiple imputation in big identifiable data for educational research: An example from the Brazilian education assessment system - Ferrão, Maria Eugénia (2020)
Submitted by SOUSA (pprata@ubi.pt) on 2020-10-25T16:49:00Z No. of bitstreams: 1 publicado-1809-4465-ensaio-S0104-40362020002802346.pdf: 1371439 bytes, checksum: b183ff773bc4f4619915df1e3e000176 (MD5)